Effect of autologous platelet rich plasma on non-surgical periodontal therapy for periodontitis in selected pakistani patients with uncontrolled type-ii diabetes mellitus - Athar, Yousaf (2023)
The susceptibility to periodontal disease is often cited as the “sixth complication of diabetes mellitus” making it the most common oral complication of diabetes. Treatment for periodontal disease includes various non-surgical and surgical approaches. The metabolic disturbances in diabetic patients may lower their resistance to infections and may help in both initiation and progression of developing inflammatory periodontal disease. The use of autologous platelet concentrates has exhibited considerable promise as a conservative therapy towards periodontal treatment. The objective of the study was to evaluate the effects of platelet rich plasma placement in deep periodontal pockets, following non-surgical periodontal therapy (NSPT) in patients with standardized uncontrolled type II diabetes. The study groups comprised two patient groups receiving non-surgical periodontal therapy and platelet rich plasma in two different concentrations and a control group receiving NSPT only. An inter and Intra group comparison of Periodontal parameters including periodontal pocket depth, alveolar bone loss and gingival index along with pro-inflammatory cytokine, Tumour Necrosis Factor Alpha (TNF-α), interleukin 1β (IL-1 β) levels and C-reactive protein levels was conducted at 45- and 90-day interval. Overall average age was 50.17 with SD = 7.13. Both interventional groups exhibited statistically significant gain in bone height. PRP 1 group showed maximum gain in alveolar bone levels. A trend towards lower HbA1c levels was shown after NSPT and adjunctive PRP placement. The PRP groups exhibited lower the levels of circulating C- reactive protein. This reduction in levels of pro-inflammatory cytokines in plasma and improved periodontal parameters indicated a conducive environment towards periodontal tissue healing and improved diabetic control.